Faktor Utama Penghambat Penerapan Manajemen Risiko Biaya pada Pelaksanaan Proyek Konstruksi Gedung Bertingkat di Surabaya dengan Menggunakan Metode AHP Fuzzy - Tia Herlina Sugiharto; Michella Beatrix (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
The implementation of risk management is an important method that is carried out in order to identify risk factors that may arise during the implementation of the project. However, the implementation of risk management still faces some obstacles in its implementation. Therefore, this study aims to analyze the barriers to the implementation of risk management in construction projects in Surabaya. A total of 80 respondents filled out questionnaires from construction service providers including contractors and consultants. Respondents involved include professional experts such as Project Managers, Site engineers, Site managers, implementers, estimators, General Managers and Company Directors. Data processing using fuzzy AHP method as a data processing tool and decision making. The results of the study revealed that the main factors that can hinder the implementation of cost risk management are inaccurate cost estimates (Y4) with the highest weight of 0.433, lack of quality Control (Qc) supervision criteria (Y5) is ranked second with a weight of 0.288, poor coordination between stakeholders (owner,contractor and consultant) (Y1) is ranked third with a weight of 0.274, lack of risk management training (Y3) is ranked fourth with a weight of 0.005, and some, old age) (Y2), the work can not be done according to the work drawings (Y6), limited skilled human resources (Y7), materials not according to specifications (Y8), improper initial cost estimation (Y9), late progressive payment from the owner (Y10) ranked fifth jointly because it has an equivalent weight value of 0.These findings conclude that accurate cost estimation (Y4) is very important in construction projects because it becomes the main basis in budget planning, decision making, and risk management.